A Static Balance Model and Analysis of 430 Stainless Steel Produced by Basic Oxygen Furnace–Argon Oxygen Decarburization Furnace Process. Issue 7 (6th May 2022) - Tian, Bohan; Zhu, Rong; Zhou, Yun; Wei, Guangsheng; Dong, Kai
Abstract : Herein, a static mass and energy balance model of 430 stainless steel (SS) produced by the basic oxygen furnace (BOF)–argon oxygen decarburization furnace (AOD) process is established and verified by plant data. It is found that in the AOD, the energy input is efficiently utilized, the heat available for other uses is relatively low (4.0%), and the addition of SS scrap is limited. The high carbon content of dephosphorization hot metal (DPHM) and post‐combustion ratio (PCR) in AOD are conducive to promoting the recycling of SS scrap. In contrast, when the carbon content of DPHM and PCR is low, it is necessary to add an exothermic agent to the furnace. Due to the saving of nickel‐containing raw materials and China's high proportion of thermal power, the carbon emissions and energy consumption per ton 430 SS produced by the BOF–AOD process are 3131 kg‐CO2 and 24 161 MJ, which is much lower than per ton 304 SS produced by the electric arc furnace (EAF)–AOD process. Meaning the former is more conducive to the promotion of energy conservation and emission reduction. Abstract : A static balance model of the basic oxygen furnace–argon oxygen decarburization furnace (BOF–AOD) process is established to guide the addition of ferrosilicon, lime and stainless steel scrap. Furthermore, compared with the electric arc furnace–argon oxygen decarburization furnace (EAF–AOD) process, this process is more conducive to energy conservation and emission reduction.